Effects of manipulated levels of predation threat on parental provisioning and nestling begging. (24th April 2019) - Mutzel, Ariane; Olsen, Anne-Lise; Mathot, Kimberley J; Araya-Ajoy, Yimen G; Nicolaus, Marion; Wijmenga, Jan J; Wright, Jonathan; Kempenaers, Bart; Dingemanse, Niels J
Abstract: Parental provisioning behavior is a major determinant of offspring growth and survival, but high provisioning rates might come at the cost of increased predation threat. Parents should thus adjust provisioning activity according to current predation threat levels. Moreover, life-history theory predicts that response to predation threat should be correlated with investment in current reproduction. We experimentally manipulated perceived predation threat in free-living great tits ( Parus major ) by presenting parents with a nest predator model while monitoring different aspects of provisioning behavior and nestling begging. Experiments were conducted in 2 years differing greatly in ecological conditions, including food availability. We further quantified male territorial aggressiveness and male and female exploratory tendency. Parents adjusted provisioning according to current levels of threat in an apparently adaptive way. They delayed nest visits during periods of elevated perceived predation threat and subsequently compensated for lost feeding opportunities by increasing provisioning once the immediate threat had diminished. Nestling begging increased after elevated levels of predation threat, but returned to baseline levels by the end of the experiment, suggesting that parents had fully compensated for lost feeding opportunities. There was no evidence for a link between male exploration behavior or aggressiveness and provisioning behavior. In contrast, fast-exploring females provisioned at higher rates, but only in the year with poor environmental conditions, which might indicate a greater willingness to invest in current reproduction in general. Future work should assess whether these personality-related differences in delivery rates under harsher conditions came at a cost of reduced residual reproductive value. Abstract : Parental provisioning increases offspring survival but might attract predators towards adults and offspring. We show that parent birds reduce provisioning initially in response to a model nest predator, but compensate for lost feeding opportunities once the immediate threat has diminished. Mothers that worked harder to provision young at higher levels were also the ones more willing to take risks in nonprovisioning contexts, suggesting individual differences in how the trade-off between current and future reproduction is resolved.